The secreted protein kinase CstK from Coxiella burnetii influences vacuole development and interacts with the GTPase-activating host protein TBC1D5 - Martinez, Eric (J Biol Chem, 2020)
The intracellular bacterial pathogen Coxiella burnetii is the etiological agent of the emerging zoonosis Q fever. Crucial to its pathogenesis is type 4b secretion system–mediated secretion of bacterial effectors into host cells that subvert host cell membrane trafficking, leading to the biogenesis of a parasitophorous vacuole for intracellular replication. The characterization of prokaryotic serine/threonine protein kinases in bacterial pathogens is emerging as an important strategy to better understand host–pathogen interactions. In this study, we investigated CstK (for Coxiella Ser/Thr kinase), a protein kinase identified in C. burnetii by in silico analysis. We demonstrate that this putative protein kinase undergoes autophosphorylation on Thr and Tyr residues and phosphorylates a classical eukaryotic protein kinase substrate in vitro. This dual Thr-Tyr kinase activity is also observed for a eukaryotic dual-specificity Tyr phosphorylation-regulated kinase class. We found that CstK is translocated during infections and localizes to Coxiella-containing vacuoles (CCVs). Moreover, a CstK-overexpressing C. burnetii strain displayed a severe CCV development phenotype, suggesting that CstK fine-tunes CCV biogenesis during the infection. Protein–protein interaction experiments identified the Rab7 GTPase-activating protein TBC1D5 as a candidate CstK-specific target, suggesting a role for this host GTPase-activating protein in Coxiella infections. Indeed, CstK co-localized with TBC1D5 in noninfected cells, and TBC1D5 was recruited to CCVs in infected cells. Accordingly, TBC1D5 depletion from infected cells significantly affected CCV development. Our results indicate that CstK functions as a bacterial effector protein that interacts with the host protein TBC1D5 during vacuole biogenesis and intracellular replication.